Graduate training in school psychology: Applied behavior analysis and autism spectrum disorder. Issue 6 (25th January 2023) - Marshall, Amanda P.; Ding, Yi; Harris, Abigail; Zusho, Akane; Shen, Yangqian; Wu, Ying
Abstract: This study investigated school psychologist's professional self‐efficacy in working with students with autism spectrum disorders (ASD), applied behavioral analysis (ABA), and other general domains. This study recruited 215 specialist and doctoral level school psychologists or school psychology interns. The Applied Behavior Analysis Efficacy Scale (ABAES) was modeled after the Huber Inventory of Trainee Self‐Efficacy (HITS). Contributions of training quality, amount of training, and knowledge of ASD to predicting professional self‐efficacy measured by the HITS and ABAES were examined. The vicarious experiences during field training were the greatest predictor of self‐efficacy in general duties and ABA‐based tasks. Mastery experiences were found to predict self‐efficacy in ABA based tasks and imaginal experiences were predictive of self‐efficacy in general duties. Field experiences were the most impactful aspect of training, but concerns were raised about disparities in experience quality. Suggestions for graduate training of school psychologists are provided. Practitioner points: 1. The vicarious experiences during field training were the greatest predictor of self‐efficacy in general duties and applied behavioral analysis (ABA)‐based tasks. 2. Mastery experiences were found to predict self‐efficacy in ABA based tasks and imaginal experiences were predictive of self‐efficacy in general duties. 3. Field experiences were the most impactful aspect of training.